Perbedaan Literasi (Pengetahuan dan Pengambilan Keputusan) tentang Kanker melalui Metode Ceramah dan Konseling pada Masyarakat: Differences in Cancer Literacy (Knowledge and Decision Making) through Lecture and Counseling Methods in the Community - Laili Rahayuwati; Kusman Ibrahim; Ikeu Nurhidayah; Dyah Setyorini (Fakultas Keperawatan Universitas Andalas, 2017)
The high prevalence and incidence of breast cancer in Indonesia remains a disheartening issue, for it has turned out to be a threat for the quality of Indonesian women’s life. The aim of this study is to develop the communities’ literacy to have more concern to prevent the health problems especially cancer that has spreading increasingly widespread in the community. The health education through lecture, discussion, and councelling of cervical cancer were conducted in this study to increase literacy on cancer. The result showed that the characteristic of women who attended the counseling and early detection examination of cervical cancer was 46– 55 years old as many as 23 respondents (38.33%). This suggests that adult women are more interested than others. In the education level showed that the high school level were 26 respondents (43.3%). The result of test of this study found that 29 respondents (48.33%) were high score of pre-test result while in the post-test result found 23 respondents (38.33%) were medium score. The different scores between the pre-test and post-test because of various factors. The activity of health education and learning intensively to the community has positive impact, the public becomes awareness on information, increase knowledge on cervical cancer, particularly in the cancer prevention and improve the quality of life among patients with cancer.